The effect of self-acupressure on pain, fatigue, and quality of sleep in patients with multiple myeloma: A randomized controlled trial - Turan, Gulcan Bahcecioglu; Ulupinar, Melih (Elsevier Science Inc, 2026)
Introduction: Multiple myeloma patients experience significant symptom burden that requires supportive, non-pharmacological approaches. This study examined the effects of self-acupressure on pain, fatigue, and sleep quality in patients with multiple myeloma. Methods: The randomized controlled study was performed between June 2023 and 2024 with 60 multiple myeloma patients randomly assigned in a 1:1 ratio using simple randomization via an online random number generator (30 in the Study Group and 30 in the Control Group).The patients in the Study Group (SG) were asked to apply 16 sessions of HT7, SP36, LI4, and SP6 points, for 18 min, 2 days per week, in the morning and evening, for 4 weeks. No interventions wer eemployed in the Control Group (CG). Pain intensity was assessed using a 10-cm Visual Analog Scale (VAS) for pain intensity, fatigue with the Piper Fatigue Scale, and sleep quality with the Pittsburgh Sleep Quality Index (PSQI). Results: Following the self-acupressure, the SG showed reductions compared to the CG in VAS for pain intensity (between-group mean difference-3.43, 95 % CI-3.92 to-2.94), Piper Fatigue Scale total score (between-group mean difference-1.80, 95 % CI-2.13 to-1.47), and PSQI total score (between-group mean difference-4.07, 95 % CI-5.11 to-3.03) and sub-dimension scores. Adverse events (AEs) were monitored throughout the study, and no AEs related to the intervention were reported. Conclusion: The results suggest that self-acupressure is effective in improving pain, fatigue, and sleep quality in patients with multiple myeloma. It is recommended that self-acupressure be used for managing patients with multiple myeloma in nursing practices, as it is an accessible and inexpensive modality. Trial registration: ClinicalTrials.govIdentifier: NCT05842265.
Keywords: Multiple myeloma; Pain; Nurse; Fatigue; Sleep quality; Self-acupressure